Assessing the Quality of the Expenditure Data Collected in the Self-Completion Questionnaire - Sun, C; Wilkins, R (My University, 2010)
The primary motivation for the collection of expenditure data is interest in the level of households’ consumption rather than their expenditure per se. This in part explains the differential time frames for measurement of expenditure. Expenditure on non-durables purchased on a reasonably regular basis are obtained for weekly or monthly time frames, whereas for durables and other items typically bought infrequently and/or irregularly, annual expenditure is obtained. Nevertheless, even if all items of household expenditure are captured by the survey, measured expenditure will not equal consumption. This is because of the existence of in-kind provision of consumption goods and services, such as occurs to a significant extent with health and education, and also because many durables, such as motor vehicles, electrical appliances and furniture, are consumed over periods longer than one year. However, given the focus of this paper is on the quality of the expenditure data, rather than on its ability to measure consumption, we restrict our attention to how well the HILDA Survey measures household expenditure over the time frames it adopts.
HILDA PROJECT DISCUSSION PAPER SERIES No. 1/10, April 2010
Keywords: Income & Finance -- Expenditure and constraints on expenditure; Surveys and Survey Methodology -- Questionnaire development; Surveys and Survey Methodology; Surveys and survey methodology; Income, wealth and finances; Income & Finance; Surveys and Survey Methodology; Expenditure and constraints on expenditure; Questionnaire development; Income, wealth and finances; Surveys and Survey Methodology